Assessment Of Topographic Variation In UMP Gambang Campus Using Drone Technology - Muhammad Naif, Saida (2023)
Maps using three distinct techniques to determine which technique is best accurate for topography. The research was conducted at the Pahang University of Malaysia. In addition, it is possible to update the data on the research area for reasons of future development. This research uses two types of methods and three different methods, namely conventional and modern methods. The land survey method, drone technology, and the digital elevation method are examples (DEM). These three methods will occur simultaneously and at the same location. In addition, the location of this event's occurrence varies from close to the study area to far from the study region. Overall, the data results were presented with their own software in accordance with the used methodology. Included among the involved software are Agisoft Metashape, QGIS, Google Pro, and Quick Grid. This application will display both 3D and 2D mapping. In addition, the selection will explain the topographical pattern, elucidating whether it is hilly or flat. Using the conventional approach and the current way, it will be feasible to determine which method is the most accurate for calculating the topographic variation at the UMP Gambang Campus. Through such evaluations, it has been determined that the traditional method is more accurate than the topographic method. In addition, this method is quite exact, as they run on the ground rather than via the air or technology in a virtual world.